Measuring Adherence to Key Teaching Techniques in an Evidence-Based Treatment: A Comparison of Caregiver, Therapist, and Behavior Observation Ratings. (June 2020) - Herschell, Amy D.; Quetsch, Lauren B.; Kolko, David J.
Traditionally, treatment adherence has been measured in outcome studies by highly trained, independent raters who code audio- or video-taped treatment sessions to understand therapists' adherence to preestablished treatment session components. Unfortunately, this method of assessing treatment adherence is time-, labor-, and cost-intensive, and does not translate well to community settings. This study compared expert-coded behavior observations, therapist and caregiver report of therapists' adherence to nine teaching technique items assessed in treatment sessions using Alternatives for Families: A Cognitive Behavioral Therapy (AF-CBT) to determine whether other raters (outside of traditional expert coders) could effectively and accurately measure therapist adherence. A total of 533 therapy sessions were coded across experts ( n = 2), therapists ( n = 20), and caregivers ( n = 42). Outcomes indicated strikingly different ratings across all reporters suggesting that therapist and caregiver reports may be supplement to, but not substitute for, observer ratings.